2009
DOI: 10.4314/tjpr.v8i4.45225
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Recrystallized Agglomerates of Cefuroxime Axetil Prepared by Emulsion Solvent Diffusion Technique

Abstract: Purpose: To study the effect of different polymers on the solubility and dissolution rate of cefuroxime axetil (CFU) prepared by emulsion solvent diffusion (ESD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The two most commonly used techniques of spherical crystallization are wet spherical agglomeration method (WSA), quasi-emulsion solvent diffusion method (QESD, Transient emulsion) 10 . But there are two extensions of these techniques, ammonia diffusion system (ADS) and crystalco-agglomeration technique (CCA) 12,13. Another technique of this process is Neutralization, where first fine crystals form by neutralization then it will agglomerate by the help of a bridging liquid 14 .…”
Section: Methods Of Spherical Crystallizationmentioning
confidence: 99%
“…The two most commonly used techniques of spherical crystallization are wet spherical agglomeration method (WSA), quasi-emulsion solvent diffusion method (QESD, Transient emulsion) 10 . But there are two extensions of these techniques, ammonia diffusion system (ADS) and crystalco-agglomeration technique (CCA) 12,13. Another technique of this process is Neutralization, where first fine crystals form by neutralization then it will agglomerate by the help of a bridging liquid 14 .…”
Section: Methods Of Spherical Crystallizationmentioning
confidence: 99%
“…The results of solubility study revealed that solubility increases with increase in concentration of carrier. Reasons for this might be improved wettability and porosity, decreased primary particle size and partial amorphization of drug in dispersed state compared to raw crystals of CC 26 . Enhanced solubility and dissolution rate of CC in SD prepared using PVP could be attributed to the chemical structure of highly water soluble PVP.…”
Section: Solubility Determinationmentioning
confidence: 99%
“…bridging liquid; and the last one is immiscible with the drug substance i.e. bad solvent 32 . The spherical crystallization has been applied to several drugs, and it has been found that the product properties are quite sensitive to the amount of the bridging liquid 15 .…”
Section: Techniques Of Spherical Crystallizationmentioning
confidence: 99%